We can't save you : [large type] a tale of politics, murder, and Maine - Ricks, Thomas E. ([Ryan Tapia], 2025)
"When a group of young Native Americans launches a series of protests against climate change and its effects on the waters and woods of Maine, veteran FBI agent Ryan Tapia is assigned to monitor the movement. When the marchers begin making camps on the lawns of luxurious summer mansions along the Maine coast, they win national media attention -- and the wrath of a reactionary president. Tapia soon finds himself torn. His bosses at the Bureau are eager to please a president itching to crack down on them. But, growing increasingly sympathetic to the protesters and their cause, Tapia lets slip about a possible refuge -- a secret CIA base hidden away in the depths of the Maine woods on the Canadian border. Enraged by the protesters' actions, the White House federalizes a Maine National Guard unit to surround and detain them on their march north. Meanwhile, Tapia's bosses, vexed and embarrassed, fire him and threaten arrest. Undaunted, Tapia snowmobiles through the wilderness on a wintry night to warn the protesters of the impending attack."--